A study on behavior intention of halal food consumption among Generation Y in Bandaraya Melaka / Asmizatie Azman, Liana Mansor and Najihah Mohamad Yusoff - Azman, Asmizatie; Mansor, Liana; Mohamad Yusoff, Najihah (2015)
Consuming halal food among generation Y Muslim is a crucial issue when it comes to Muslims. This study focuses on the influences, which are subjective norm, attitude and perceived behavioral intention that give the greatest impact towards generation Y while consuming halal food. The aim of this study is to determine the most effective influences, in facts, the consuming behavior among generation Y. To analyze the data, the researcher used SPSS software version 21.0. According to the results, the most effective tourism development is through its environmental (0.620), followed by social (0.616), cultural (0.478), and economic (0.449). 150 overall respondents have participated in the study questionnaire. The study has found that there is a relationship between influences with Generation Y when consuming food.